Contrast Induced Nephropathy in Diabetic and Non-diabetic Patients during Coronary Angiogram and Angioplasty (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):372-6The abstract of this article is available on the PubMed website